Implementation of Delone & Mclean is Success Model as an Evaluation of Resource Management Information System at Dapoer Widya - Suryantari, Putu Anggi; Safira, Amalia; Sakha Nesya Arimawan, Kesya; Wulansari, S.Kom., M.Kom, Anita; Ayu Sri Deviyanti, ST., MT, I Gusti (NAROTAMA UNIVERSITY, 2023)
This study aimed to analyze the steps contained in the updated model. The model includes six interrelated dimensions of information system (IS) success, namely system quality, information quality, service quality, user satisfaction, and net benefits. The research method used is an explanation with a quantitative approach. The type of research conducted is a survey, where data is collected through filling out questionnaires through Google Form. The data used in the study was collected between January and March 2023. The study sample consisted of 96 respondents who had filled out questionnaires. The results showed that hypothesis 1 was accepted, which showed that the quality of information had a positive effect on customer satisfaction, with a P-Values value of 0.012. However, hypothesis 2 was rejected, which showed that the quality of the system had no effect on customer satisfaction, with a P-Values of 0.185. Furthermore, hypothesis 3 is accepted, indicating that service quality positively affects customer satisfaction, with a P-Values of 0.000. Hypothesis 4 is also accepted, which shows that customer satisfaction positively affects net benefits, with a P-Values of 0.000. Keywords: net benefit, user satisfaction, information quality, service quality, system quality